Adolescent Peer Experiences and Prospective Suicidal Ideation: The Protective Role of Online-Only Friendships. Issue 1 (2nd January 2022) - Massing-Schaffer, Maya; Nesi, Jacqueline; Telzer, Eva H.; Lindquist, Kristen A.; Prinstein, Mitchell J.
Abstract: Objective : This study examined characteristics of online-only friendships among suicidal and non-suicidal adolescents. In addition, the extent to which adolescents' online-only friendships may offer a protective function, buffering the effects of peer stressors (i.e., friendship stress, relational victimization) on prospective suicidal ideation, was examined. Method : Adolescents aged 10 to 14 (n = 630) were assessed at baseline (Time 1) and one-year follow-up (Time 2). Measures of suicidal ideation, sociometric relational victimization, friendship stress, depressive symptoms, online-only friendship status and quality, and online-only friendship quality compared to in-person friendship quality, were obtained at Time 1 using sociometric procedures and self-report questionnaires. Self-report measures of suicidal ideation were collected at Time 2. Results : Descriptive results suggested that online-only friendships are relatively common among youth (38.3%), particularly for those experiencing suicidal ideation (46.3%). Suicidal and non-suicidal adolescents reported comparable levels of intimate disclosure within their online-only friendships. Although adolescents without suicidal ideation endorsed more support from in-person friendships, suicidal adolescents endorsed similar levels of support from their online-only and in-person friendships. Moderation analyses indicated that the association between both relational victimization and friendship stress and prospective suicidal ideation was attenuated among youth who reported having one or more online-only friend. Conclusion : Online-only friendships are common and may offer protective benefits for youth, particularly those experiencing suicidal ideation. Future studies should examine the specific mechanisms by which online-only friendships may confer this benefit.